Regional amyloid accumulation predicts memory decline in initially cognitively unimpaired individuals. Issue 1 (2nd August 2021) - Collij, Lyduine E.; Mastenbroek, Sophie E.; Salvadó, Gemma; Wink, Alle Meije; Visser, Pieter Jelle; Barkhof, Frederik; van Berckel, Bart. N.M.; Lopes Alves, Isadora
Abstract: Introduction: The value of quantitative longitudinal and regional amyloid beta (Aβ) measurements in predicting cognitive decline in initially cognitively unimpaired (CU) individuals remains to be determined. Methods: We selected 133 CU individuals with two or more [ 11 C]Pittsburgh compound B ([ 11 C]PiB) scans and neuropsychological data from Open Access Series of Imaging Studies (OASIS‐3). Baseline and annualized distribution volume ratios were computed for a global composite and four regional clusters. The predictive value of Aβ measurements (baseline, slope, and interaction) on longitudinal cognitive performance was examined. Results: Global performance could only be predicted by Aβ burden in an early cluster (precuneus, lateral orbitofrontal, and insula) and the precuneus region of interest (ROI) by itself significantly improved the model. Precuneal Aβ burden was also predictive of immediate and delayed episodic memory performance. In Aβ subjects at baseline ( N  = 93), lateral orbitofrontal Aβ burden predicted working and semantic memory performance. Discussion: Quantifying longitudinal and regional changes in Aβ can improve the prediction of cognitive functioning in initially CU individuals.